Conjunctive epidermis carcinoma: A case presentation. - Yaney Gonzalez Iglesias; Hernán García Alvarez; Bárbara Ríos Araujo; Bárbara Suárez Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Epidermoid carcinoma of conjunctiva in man of 78 years old presents case itself of with little inhabitual presentation for these patient. Patient that encounters was present whit an episode of blennorrhagic conjunctivitis that is treated initially by this cause and that progresses of inhabitual form. The histopathology exam revealed an epidermoid conjunctiva carcinoma. The evolution of this patient was rapid and invasive, he was treated with an orbital exenteration and suprahomohiodeo drain and he is waiting for radiotherapy treatment.